1992
DOI: 10.1029/92gl00403
|View full text |Cite
|
Sign up to set email alerts
|

IMF draping around the Geotail: IMP 8 observations

Abstract: This paper gives maps of magnetosheath magnetic field lines in a roughly 12RE thick annulus circling the tail approximately 30RE downwind from Earth. There are maps for northward and southward IMF and for quasi‐equatorial IMF (the usual case). The maps are based on IMP 8 data taken during the 127 orbits (four years) when ISEE 3 measured the upstream IMF. In these four years, IMP 8's orbit swept the mapped annulus eight times. The maps project the field onto a plane perpendicular to the sun‐earth line, after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 11 publications
4
37
1
Order By: Relevance
“…They also showed that the angle between the IMF direction and the separatrix in the magnetosheath where two topologically dierent ®elds (from the magnetosphere and from the magnetosheath) meet increases as the IMF changes its orientation from north to south. These results agrees well with the results of Kaymaz et al (1992) and encourage us to make the comparisons given in this work. We give here the ®rst comprehensive comparison between magnetosheath data and Fedder-Lyon MHD model.…”
Section: About the Mhd Modelsupporting
confidence: 81%
See 3 more Smart Citations
“…They also showed that the angle between the IMF direction and the separatrix in the magnetosheath where two topologically dierent ®elds (from the magnetosphere and from the magnetosheath) meet increases as the IMF changes its orientation from north to south. These results agrees well with the results of Kaymaz et al (1992) and encourage us to make the comparisons given in this work. We give here the ®rst comprehensive comparison between magnetosheath data and Fedder-Lyon MHD model.…”
Section: About the Mhd Modelsupporting
confidence: 81%
“…Because the magnetic forces become dominant in the inner dayside magnetosheath and because the geomagnetic ®eld interconnects with the IMF and violates the gas dynamic model assumption of an impenetrable magnetopause boundary, magnetic reconnection particularly aects the ®eld draping geometry at the magnetopause as shown in Kaymaz et al (1992) for IMFs in the equatorial plane. Further, the ®eld structure is dierent qualitatively and quantitatively for northward and southward IMFs.…”
Section: About the Gas-dynamic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A more global study by Kaymaz et al [1992] examines the magnetic field data from IMP 8 and ISEE-3 and shows that the draping pattern of magnetic field lines in the magnetosheath is heavily dependent on the interplanetary magnetic field (IMF) orientation. They also conclude that northward and southward IMF directions have significant and different effects on the character of the magnetic field inside the magnetosheath.…”
Section: Introductionmentioning
confidence: 99%